Christianity under colonialism: Mäòhi Protestantism in French Polynesia - Misaki, M (2022)
This thesis argues that colonial memories and experiences of indigenous Mäòhi Christians are the primary impetuses for the religious synthesis of imported cultural elements with indigenous traditions. Focusing on the Mäòhi Protestant Church (EPM) in French Polynesia, this work seeks to contribute to wider anthropological debates on Christianity by highlighting indigenous narratives of colonialism and resistance through the development of local expressions of Christianity. Although French Polynesia is still, to all intents and purposes, a French colony, the congregational Protestant church, which is equidistant with both French Catholicism and French laïcité, provides a space within which French colonial dominance is temporarily and spatially undermined. People’s frustration at the ongoing loss of traditional customs and values has motivated the creation of a religious space where the revival of these customs and values - justified on theological grounds - is possible. The ‘indigenisation’ of the religious sphere is a practical solution to tackle a variety of problems caused by colonialism, such as the dissolution of community bonds, the loss of the indigenous language, and radioactive pollution from atomic experiments. Navigating through such challenges, Mäòhi Christians self-reflexively negotiate the cultural, theological, and temporal hybridity of their religious expressions. My participation in everyday activities in the parishes of Moorea and Rurutu island revealed that the ongoing experience of colonialism, combined with memories of colonisation, is the major motivation for their conscious remaking of the Christian religion.